Experimental Research on Antiseismic Performance of High-Strength Concrete High-Shear Walls with Built-In Steel Plates. (20th June 2019) - Yu, Yu; Gan, Min; Zhang, Yan; Li, Liren; Zhang, Huakun
Abstract : To study the antiseismic performance of the high-strength concrete composite shear wall with built-in steel plates, an experiment on a high-strength concrete composite shear wall with four built-in steel plates (SPRCW-1∼4) was set up. Based on the experimental result, the paper discusses the antiseismic performance, failure mode, and failure mechanism of the high-strength concrete composite shear wall with built-in steel plates under different steel ratios and different positions of steel plates. The experimental result has shown that the differences in steel plate position and steel ratios have certain effects on wall cracking. The use of high steel content and the placement of steel plates on both sides of the wall can limit wall cracking to some extent. When the bearing capacity of the steel plates located on both sides of the wall is larger than that in the middle of the wall, a high content of steel in the wall can effectively increase the bearing capacity of the test piece to some extent. Under a high axial compression ratio, the horizontal bar of the wall can substantially limit the vertical cracks in concrete arising from compression. Moreover, the built-in steel plates in the shear wall play a significant role in inhibiting the propaganda of the oblique cracks under the action of earthquakes. The research result has very good economy and operability and can provide a basis for promotion and application of the mid- and high-rise buildings in regions with high seismic intensity.